Fertility impairment in radiotherapy - Biedka, Marta; Kuźba-Kryszak, Tamara; Nowikiewicz, Tomasz; Żyromska, Agnieszka (Contemporary Oncology/Współczesna Onkologia, 2016)
Infertility as a result of antineoplastic therapy is becoming a very important issue due to the growing incidence of neoplastic diseases. Routinely applied antineoplastic treatments and the illness itself lead to fertility disorders. Therapeutic methods used in antineoplastic treatment may cause fertility impairment or sterilization due to permanent damage to reproductive cells. The risk of sterilization depends on the patient’s sex, age during therapy, type of neoplasm, radiation dose and treatment area. It is known that chemotherapy and radiotherapy can lead to fertility impairment and the combination of these two gives an additive effect. The aim of this article is to raise the issue of infertility in these patients. It is of growing importance due to the increase in the number of children and young adults who underwent radiotherapy in the past. The progress in antineoplastic therapy improves treatment results, but at the same time requires a deeper look at existential needs of the patient. Reproductive function is an integral element of self-esteem and should be taken into account during therapy planning.